If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 6 + 2d Solving 22 = 6 + 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. 22 + -2d = 6 + 2d + -2d Combine like terms: 2d + -2d = 0 22 + -2d = 6 + 0 22 + -2d = 6 Add '-22' to each side of the equation. 22 + -22 + -2d = 6 + -22 Combine like terms: 22 + -22 = 0 0 + -2d = 6 + -22 -2d = 6 + -22 Combine like terms: 6 + -22 = -16 -2d = -16 Divide each side by '-2'. d = 8 Simplifying d = 8
| 8+3B=-1 | | -8(x+5)+7(2x+1)= | | -3/2(2y+6)=15 | | .018x+0.09y=(360)(0.16) | | 65x+300=47x | | r^2+3r-28= | | 1/2(x-11)=9 | | 2g-5=26 | | .06x+0.10y=(240)(0.08) | | 5k^2+6k-11=0 | | 5s^2-31s=28 | | 5k^2+16k-11=0 | | 5k^2+16k+11=0 | | 4x^9y^7+16x^7y^6+28xy= | | 5k^2-4k-1=0 | | (7x+3)=(4x+1) | | t^2-10t+21=0 | | 6x+13=43 | | 4=1i+0.5i | | (-2+x)(5x-2)= | | ys+yv=x | | 19x-5=7+13x | | 6.1x-3=5.1x | | (6cd^2+4cd)-(3cd^2-9cd^2-9cd+5)= | | 6+6q=9+5q | | c^2+6cg-27g^2=0 | | 7+(-5+4q)+(-7q-4)= | | (4x-3)(x-5)=0 | | 12x+4=6x+14 | | 3[x-2(x-5)]-1=-3x+29 | | y^2-3y-28=0 | | 6(w-5)=8w+44 |